2022
DOI: 10.1101/2022.01.11.475795
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimized cell culture conditions promote ex-vivo manipulation and expansion of primitive hematopoietic stem cells for therapeutic gene editing

Abstract: During the last few years, gene editing has emerged as a powerful tool for the therapeutic correction of monogenic diseases. CRISPR/Cas9 applied to hematopoietic stem and progenitor cells (HSPCs) has shown great promise in proof-of-principle preclinical studies to treat haematological disorders, and clinical trials using these tools are now underway. Nonetheless, there remain important challenges that need to be addressed, such as the efficiency of targeting primitive, long-term repopulating HSPCs and expand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Indeed, it is well known that prolonged culture and stimulation of HSPCs, while being needed for efficient gene transfer, may adversely impact their engraftment and long-term repopulation capacity. Recent findings showed that addition to the culture medium of stemness preserving compounds, such as Stem Regenin-1, UM171, and 16,16-dimethyl prostaglandin E2 (dmPGE2), helps to maintain the long-term multilineage repopulation capacity of human corrected HSPCs transplanted in immunodeficient mouse models, partially overcoming the drawbacks of prolonged culture ( 96 ) and that fine-tuning of cytokine composition can lead to a beneficial balance between preservation of stemness and cell expansion ( 115 , 116 ). Another aspect that needs special attention is the tolerability of HSPCs to genetic modifications; indeed LT-HSCs, which require protection from mutational load over a lifetime, are more sensitive to DNA manipulation than differentiated cells, hence GE may trigger cellular responses that reduce their fitness and stemness.…”
Section: Outstanding Challenges In the Field Of Hsc Gene Editingmentioning
confidence: 99%
“…Indeed, it is well known that prolonged culture and stimulation of HSPCs, while being needed for efficient gene transfer, may adversely impact their engraftment and long-term repopulation capacity. Recent findings showed that addition to the culture medium of stemness preserving compounds, such as Stem Regenin-1, UM171, and 16,16-dimethyl prostaglandin E2 (dmPGE2), helps to maintain the long-term multilineage repopulation capacity of human corrected HSPCs transplanted in immunodeficient mouse models, partially overcoming the drawbacks of prolonged culture ( 96 ) and that fine-tuning of cytokine composition can lead to a beneficial balance between preservation of stemness and cell expansion ( 115 , 116 ). Another aspect that needs special attention is the tolerability of HSPCs to genetic modifications; indeed LT-HSCs, which require protection from mutational load over a lifetime, are more sensitive to DNA manipulation than differentiated cells, hence GE may trigger cellular responses that reduce their fitness and stemness.…”
Section: Outstanding Challenges In the Field Of Hsc Gene Editingmentioning
confidence: 99%